Landscape of targets within nucleoside metabolism for the modification of immune responses - Dunderdale, Ella M.; Abt, Evan R. (Frontiers in Oncology, 2025)
Nucleoside metabolism regulates immune cell development and function, but the therapeutic implications of this link have yet to be fully realized. Evidence for the importance of nucleoside metabolism in immune system control was provided by observations of immunodeficiency and autoimmunity across patients with genetic errors that alter nucleoside synthesis or breakdown. Research over the past several decades has uncovered a multifaceted role for nucleosides in mediating immune responses that involves their function as metabolic precursors and as ligands for immune receptors. These findings prompted the development of treatments that block the production of the immunosuppressive nucleoside adenosine for cancer immunotherapy. Guanosine and pyrimidine nucleosides also mediate immune outcomes, and the key regulators of their metabolism are promising new targets to unleash anti-cancer immune responses or dampen autoimmune reactions. This review provides an overview of (i) recent research concerning the mechanisms underlying nucleoside-mediated immune regulation, (ii) the current landscape of therapeutic targets for immune modulation within nucleoside metabolism, and (iii) opportunities for developing improved preclinical models that recapitulate human nucleoside metabolism, which are needed to advance new metabolism-targeting therapies toward the clinic.